2008
DOI: 10.2137/145960609789267579
|View full text |Cite
|
Sign up to set email alerts
|

Use of secondary somatic embryos promotes genetic fidelity in cryopreservation of cocoa (Theobroma cacao L.)

Abstract: The inability to conserve cocoa (Theobroma cacao L.) germplasm via seed storage and the vulnerability of field collections make the establishment of cryopreserved genebanks for the crop a priority. An effective encapsulation-dehydration based cryopreservation system has been developed for cocoa but because the somatic embryos used for freezing arise after a protracted period of callus culture there is concern about maintenance of genetic fidelity during the process. Microsatellite markers for seven of the 10 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 17 publications
(21 reference statements)
4
17
0
Order By: Relevance
“…However, deciphering global hyper/hypomethylation from restriction products is not a reliable approach ( Fulneček and Kovařík, 2014 ). What is more, other studies have shown that methylation levels during in vitro propagation are related to the donor tissue ( Fang et al, 2009 ; Wang et al, 2012 ), to the length of the culture ( Diaz-Sala et al, 1995 ; Rodríguez López et al, 2010a , b ), and the media components ( LoSchiavo et al, 1989 ; Arnholdt-Schmitt, 1993 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, deciphering global hyper/hypomethylation from restriction products is not a reliable approach ( Fulneček and Kovařík, 2014 ). What is more, other studies have shown that methylation levels during in vitro propagation are related to the donor tissue ( Fang et al, 2009 ; Wang et al, 2012 ), to the length of the culture ( Diaz-Sala et al, 1995 ; Rodríguez López et al, 2010a , b ), and the media components ( LoSchiavo et al, 1989 ; Arnholdt-Schmitt, 1993 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to propagate elite or desirable clones is an essential part of the seed production industry. The advent of reliable in vitro systems for the replication and regeneration of plant materials has led to their widespread deployment for propagation ( Bertrand et al, 2011 ; Etienne et al, 2012 ), germplasm conservation ( Fang et al, 2009 ), and breeding purposes ( Henry, 1998 ), as well as for more fundamental research on model species ( Berdasco et al, 2008 ; De-la-Peña et al, 2012 ; Moricová et al, 2013 ). For micropropagation and genetic transformation systems to be efficient, it is necessary that the plants recovered from them are genetically and epigenetically faithful to the original stock material.…”
Section: The Potential Value Of Epi-fingerprinting For Agriculturementioning
confidence: 99%
“…Not surprisingly, our results showed an increase in variability in all in vitro cultured samples ( in vitro , 1h LN, Post 1h LN). As we have shown previously, this variability is both genetic and epigenetic in nature [12,1416,36]. More interestingly, SSE recultured after one hour in liquid nitrogen (i.e.…”
Section: Discussionmentioning
confidence: 64%
“…However, the passage of cells through in vitro culture [11] and cryopreservation [35] may lead to undesirable changes (somaclonal variation) in the regenerants. Although the effect of in vitro culture, somatic embryogenesis and cryopreservation of somatic embryos on the morphological and genetic fidelity of cocoa plants has been extensively studied [12,1416,36], very little is known about the epigenetic modifications introduced by the cryopreservation of cocoa somatic embryos. Not surprisingly, our results showed an increase in variability in all in vitro cultured samples ( in vitro , 1h LN, Post 1h LN).…”
Section: Discussionmentioning
confidence: 99%